Assessment of the Depth of the Plastically Deformed Top Layer in Burnishing Process of Shaft Using a Ceramic Tool - Piotr Paszta; Leszek Chałko; Rafał Kowalik (Advances in Mechanical and Materials Engineering)
Burnishing is one of the most effective methods of improving the strength of the surface layer of shafts as a result of strain strengthening of the material. This article presents an analytical approach to determining the the depth of the plastically deformed top layer of shaft based on Belyaev's theory. Contact of two bodies with an asymmetric stress state was assumed. A classic (symmetrical) solution was also considered. The aim of the research was to compare the calculated values of the depth of the plastically deformed top layer determined using these two methods. The calculations considered burnishing of shafts with a diameter of 48 mm made of steel with a yield stress of Re = 450 MPa and Re = 900 MPa. A burnishing tool with a Si3N4 ceramic tip was used for burnishing. It was found that in the range of low contact forces, the calculated values of the depth of the plastically deformed top layer using the asymmetric solution and the classical method are similar. It was also found that the relationship between the depth of the plastically deformed top layer and the contact force can be explained by a power equation with an accuracy of R2 > 0.999.